Pelatihan Keberlanjutan Manfaat Program Merdeka Universitas Teknologi Sumbawa di Desa Kerekeh - Salam, Abdul; Fahlia, Fahlia; Nuramaliyah, Nuramaliyah; Santoso, Agus; Maradita, Fendy; Sri Nuryani, Hanifa; Hartini, Hartini (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2023)
Sustainability of the Merdeka program aims to provide knowledge and skills in digital marketing, processing PIRT and halal product permits, training on human resources as well as tips and tricks for managing businesses in the digitalization period for MSME players in Kerekeh Village, Unter Iwes District, Sumbawa Regency, West Nusa Tenggara.The implementation was carried out by providing information services using the lecture method in the form of socialization, namely with presentation techniques. With this Community Service, it is hoped that MSME products can be quickly recognized and reach consumers which has an impact on increasing profits or production profits. The activity took place conducively, where all participants were very enthusiastic in participating in the activity from the beginning to the end of the activity. This community service activity involves cross study programs. Not only does this collaboration produce a better and more innovative model, but it also contributes more positively to the knowledge and skills of MSMEs in Kerekeh Village.